A Study on the Law of Gas Production by Pyrolysis of Mixed Insulating Oil under Simulated Overheating Condition. Issue 1 (March 2021) - Li, Guoxing; Fu, Lijun; Wang, Yue; Li, Lin; Zhang, Liang; Guan, Yanling
Abstract: To analyze the law of decomposition and gas production of mixed insulating oil under the action of heat energy, this research conducted the decomposition test of mineral insulating oil, vegetable insulating oil and mixed insulating oil at different hot-spot temperatures through the thermal fault simulation test, compared and analyzed the gas production characteristics and differences of the three insulating oils under the action of heat energy, and analyzed the pyrolysis gas production mechanism of vegetable insulating oil. According to the test results, it can be found that under the condition of no insulating paper and metal catalyst, the characteristic gases produced by the three oils under the action of heat energy are the same, mainly H2, CH4, C2 H4, C2 H6, CO, CO2 . When the temperature is higher than 700°C, a small amount of C2 H2 will be produced; when the temperature is low overheated, the pyrolysis characteristic gases of mineral insulating oil are mainly H2 and CH4, while the characteristic gases of vegetable insulating oil and mixed insulating oil are H2 and C2 H6 ; when heated, vegetable insulating oil is more easily to produce H2 than mineral insulating oil; under the same conditions, the CO and CO2 produced in the vegetable insulating oil are much more than that of the mineral insulating oil, dozens of times more at high temperature; the mixed oil presents similar characteristics to the vegetable insulating oil, which is consistent with the relatively large proportion of vegetable oil in the mixed oil.